2010
DOI: 10.4300/jgme-d-09-00096.1
|View full text |Cite
|
Sign up to set email alerts
|

Disparity Between Resident and Attending Physician Perceptions of Intraoperative Supervision and Education

Abstract: A significant proportion of surgical skills training during residency occurs as on-the-job training, and operating room time provides a key learning opportunity. This report demonstrates that there is a noteworthy difference in the perception of attending physicians and residents about the quality of teaching and feedback that is currently occurring in the operating room. The difference in perspectives among residents and attending physicians reported in this survey suggests a need for improved communication a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 9 publications
1
26
1
1
Order By: Relevance
“…Similar findings have also been found in the operative training of obstetrics and gynecology residents. 10 Previous comparison studies have also found disparities between residents and faculty with respect to intraoperative learning needs. The top 5 learning needs in the operating room as perceived by surgical residents in descending order of importance were instrument use and selection, selection of suture material, operative field exposure, patient positioning, and sequence of procedure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar findings have also been found in the operative training of obstetrics and gynecology residents. 10 Previous comparison studies have also found disparities between residents and faculty with respect to intraoperative learning needs. The top 5 learning needs in the operating room as perceived by surgical residents in descending order of importance were instrument use and selection, selection of suture material, operative field exposure, patient positioning, and sequence of procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, residents and faculty agreed that intraoperative feedback was constructive, although with a p-value of only 0.06, this might suggest a trend toward disagreement. Levinson et al 10 in their 2010 study of obstetric and gynecology residents found that faculty and residents' opinions differed most in perceptions of intraoperative feedback. In our study, a significant disparity was found between the residents and faculty with respect to both positive and negative feedback in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12,[23][24][25][26] Descriptions of Generation Y (individuals born after 1982 12 ) predict some of the attitudes expressed by our residents: For example, our residents indicated that they would like faculty to provide more specific work expectations, more support, better explanations when residents' treatment plans are changed, and frequent feedback. However, we did not design this study for generational analysis: Although most of the responding residents belong to Generation Y, the faculty are a composite of generations.…”
Section: Generational Differencesmentioning
confidence: 91%